How likely is hypokaliemia development in indapamide treatment? - V. A. Lusov; V. I. Kharchenko; E. M. Evsikov; M. V. Koryakin; M. M. Virin; А. V. Kharchenko; B. G. Potievsky; I. E. Vid'manova (Российский кардиологический журнал)
.